Adoptive T‐cell therapy targeting Epstein–Barr virus as a treatment for multiple sclerosis. Issue 3 (21st March 2023) - Smith, Corey; Khanna, Rajiv
Abstract: Emergence of a definitive link between Epstein–Barr virus (EBV) and multiple sclerosis has provided an impetus to develop immune‐based therapies to target EBV‐infected B cells. Initial studies with autologous EBV‐specific T‐cell therapy demonstrated that this therapy is safe with minimal side effects and more importantly multiple patients showed both symptomatic and objective neurological improvements including improved quality of life, reduction of fatigue and reduced intrathecal IgG production. These observations have been successfully extended to an 'off‐the‐shelf' allogeneic EBV‐specific T‐cell therapy manufactured using peripheral blood lymphocytes of healthy seropositive individuals. This adoptive immunotherapy has also been shown to be safe with encouraging clinical responses. Allogeneic EBV T‐cell therapy overcomes some of the limitations of autologous therapy and can be rapidly delivered to patients with improved therapeutic potential. Abstract : Adoptive immunotherapy targeting Epstein–Barr virus has emerged as a potential therapeutic strategy for the treatment of multiple sclerosis. We have developed a novel manufacturing process, which can offer these T‐cell therapies as an off‐the‐shelf treatment.